PENGARUH PENJUALAN DAN PERPUTARAN TOTAL AKTIVA TERHADAP LABA BERSIH PADA PERUSAHAAN SEKTOR MANUFAKTUR DI JAKARTA ISLAMIC INDEX TAHUN 2020-2024 - Muslimah Muslimah; Agustina Mutia; Faturahman Faturahman (ISTISMAR, 2026)
This study aims to analyze the effect of sales and total asset turn over on net profit in manufacturing companiest listed in the Jakarta Islamic Index (JII) during 2020–2024. The research employed a quantitative associative approach. Secondary data were collected from annual financial statements obtained from the Indonesia Stock Exchange and company websites. The sample consisted of 11 manufacturing companies selected through purposive sampling. resulting in 55 observations. data were analyzed using panel data regression with Eviews 12 software. The results indicate yhat sales have a positive and significant effect on net profit with a t-statistic of 3,992145 and a significance value 0,0032.  Total asset turnover also has a positive and significant effect on net profit with a t-statistic of 4,191791 and a significance value of 0,0023.  Simultaneously, sales and total asset turnover significantly affect net profit with an F-statistic of 7,398471 and a probability value of 0,002561. These findings imply that increasing sales and improving asset utilization efficiency contribute significantly to enhancing net profit. Keywords: Sales, total asset turnover, net profit, jakarta islamic index